Грамматическая теория в трудах М. И. Стеблин-Каменского - Иванова, И. П. (Kalbotyra, 1985)
The article is a review of the works by M. I. Steblin-Kamenskij published in the period of 1957–1974, dealing with the most important categories and methods of grammatical analysis and linguistic terminology.